Flexible Work Arrangements and Health in White-Collar Urban Professionals. (February 2021) - Senthanar, Sonja; Varatharajan, Sharanya; Bigelow, Philip
Although some research has examined health implications of flexible work arrangements, little is known about job flexibility and health in the context of modern working life, characterized by intensification. Grounded on the Job Demand-Resource model, this article explores access to flexible work arrangements and organizational climate on the health and well-being of white-collar, urban professionals in downtown Toronto. A qualitative content analysis of eight semistructured interviews with white-collar, urban professionals between the ages of twenty-five and thirty-two revealed three domains—intensity of work life and demands, coworker and managerial relations, and the boundaries between work and home—where demands outweighed resources to limit workers' ability to practice flexibility. Thus, an emerging trend where workers need to be flexible within flexible work arrangements emerged. Findings point to the need for organizational commitment and activities to address unhealthy behaviors in the context of modern working life.